Shaping viral immunotherapy towards cancer-targeted immunological cell death - Isaeva, Anastasia S.; Trujillo Yeriomenko, Adriana D.; Idota, Esther; Volodina, Sofya I.; Porozova, Natalia O.; Bezsonov, Evgeny E.; Malogolovkin, Alexander S. (Frontiers in Oncology, 2025)
BackgroundOncolytic viruses (OVs) have the ability to efficiently enter, replicate within, and destroy cancer cells. This capacity to selectively target cancer cells while inducing long-term anti-tumor immune responses, makes OVs a promising tool for next-generation cancer therapy. Immunogenic cell death (ICD) induced by OVs initiates the cancer-immunity cycle (CIC) and plays a critical role in activating and reshaping anti-cancer immunity. Genetic engineering, including arming OVs with cancer cell-specific binders and immunostimulatory molecules, further enhances immune responses at various stages of the CIC, improving the specificity and safety of virotherapy.The aim of this study is to update current knowledge in immunotherapy using OVs and to highlight the remarkable plasticity of viruses in shaping the tumor immune microenvironment, which may facilitate anti-cancer treatment through various approaches.MethodologyResearch articles, meta-analyses, and systematic reviews were retrieved from PubMed, using the search terms (‘Oncolytics’ OR ‘Immunotherapy’ OR ‘Virotherapy’ OR ‘Viral vector’) AND ‘gene therapy’, without language restrictions.ResultsIn this review, we discuss current strategies aimed at increasing the tumor specificity of OVs and improving their safety. We summarize and functionally categorize different biochemical approaches, with a focus on virus engineering and advancements in immunotherapy. Transduction targeting methods (e.g., xenotype switching, pseudotyping, cell receptor targeting) and non-transduction modifications (e.g., miRNA, optogenetics, transcriptional targeting) are critically reviewed. We also examine the mechanisms of ICD and viral modifications that contribute to efficient cancer cell death and modulation of cancer-specific immunity. Finally, we provide an outlook on promising future oncolytics and approaches with potential therapeutic benefit for the next generation of cancer immunotherapy.ConclusionImmunogenic cell death induced by oncolytic viruses is a key mediator of potent anti-cancer immunity. The genetic integration of immunostimulatory molecules as regulatory elements into OV genomes significantly enhances their therapeutic potential, safety, and stability. Additionally, therapeutic potency can be further increased by deleting viral genes that inhibit apoptosis, thereby enhancing ICD. However, the synergistic effects of these modifications may vary significantly depending on the cancer type.